Leveraging Academic Partnerships to Improve Logistics at Nonprofit Organizations. Issue 3 (31st October 2016) - Manikas, Andrew S.; Kroes, James R.; Gattiker, Thomas F.
Abstract : This article presents the results of a partnership between a nonprofit organization and a team of academic researchers that developed a low‐cost spreadsheet‐based tool that allows organizations to effectively schedule vehicle operations. Specifically, the tool (1) handles the real‐world constraints present in moderately complex logistics environments; and (2) uses general computing hardware and software that is already deployed in most organizations, thereby rendering the solution radically low cost (effectively free). We deployed this tool to a humanitarian organization, the Idaho Foodbank, which realized a substantial improvement in its fleet efficiency and a corresponding reduction in route‐planning time. The methodology used to manage this collaboration with academia can be leveraged by other nonprofit organizations attempting to overcome the financial barriers that commonly prevent budget‐constrained organizations from accessing advanced technologies.